Program uroczystości związanych z "Tygodniem Ziem Zachodnich" od dnia 13-20.IV.47 r. (Gdynia : [s.n.], 1947)
Afisz z programem uroczystości.
Keywords: Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- źródła